No evidence of oxidative stress after a triathlon race in highly trained competitors - Margaritis, I.; Tessier, F.; Richard, M. J.; Marconnet, P. (International Journal of Sports Medicine, 1997)
Long distance triathlons, due to the large amounts of oxygen uptake they cause, may lead to the generation of reactive oxygen species, and consequently to oxidative stress and damage. We sought to verify this hypothesis. Twelve of the 18 male triathletes who participated in the study took part in a long distance triathlon, the others did not. The prerace blood samples were drawn 48 h before the race and repeatedly until the fourth day of recovery. The myoglobin concentrations increased immediately after the race. The concentrations of methemoglobin, disulfide glutathione (GSSG), and thiobarbituricreactive substances did not significantly change after the race. Although the race induced an inflammatory response, evidenced by the variations in neopterin concentrations and leukocyte counts, there was no consecutive oxidative stress. The basal GSH values were correlated significantly with cycling training volume (r = 0.55) and VO2max (r = 0.53). Muscle damage can occur without evidence of oxidative stress or oxidative damage. We conclude that the magnitude of the antioxidant defense system enhancement depends on training loads. Because of their training status, the triathletes did not suffer from oxidative damage after they finished the long distance triathlon race.